COMBINING ABILITY FOR YIELD ATTRIBUTES IN GREENGRAM (VIGNA RADIATA L. WILCZEK) - R. NARASIMHULU; N. V. NAIDU; K. H. P. REDDY; G. MOHAN NAIDU (The Bioscan, 2014)
Five lines were crossed with four testers in Line × Tester fashion to estimate the combining ability for yield and yield attributing traits in greengram. Analysis of variance revealed significant differences among genotypes, crosses, lines, testers and line × tester interactions for most of the traits. Preponderance of non-additive gene effects was realized from higher values of specific combining ability compared to general combining ability and ratio of variances of SCA to GCA except for tolerance to MYMV. Parents viz., MGG-351, WGG-42, LGG-460 and TM-96-2 were considered as superior parents as they recorded high per se performance with positive significant effects for seed yield per plant and other yield contributing traits. Cross combinations viz., MGG-351 × PM-115, TM-96-2 × PM-112, MGG-295 × PM-110, TM-96-2 × WGG-37 WGG-42 × WGG-37 and WGG-42 × PM-110 were found to be good specific combinations for seed yield per plant and other desirable traits. These cross combinations could be utilized for further amelioration of seed yield in greengram.